P244 Defining the minimum clinically important difference (MCID) for the evaluating respiratory symptoms in COPD daily diary using global anchors: data from the FULFIL study. (December 2018) - Tabberer, M; Zhu, C-Q; Doyle, S; Lipson, DA
Abstract : Introduction and objectives: FULFIL was a phase III, randomized, double-blind, double-dummy trial comparing once-daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100 µg/62.5 µg/25 µg via a single ELLIPTA inhaler with twice-daily budesonide/formoterol (BUD/FOR) 400 µg/12 µg via the Turbohaler in patients aged ≥40 years with advanced, symptomatic COPD at risk of exacerbations (Lipson et al, Tabberer et al ). FULFIL collected patient reported symptom severity using the Evaluating Respiratory Symptoms in COPD [E-RS: COPD] every evening as an endpoint measurement. Patient Global Rating of Change (GRC) in COPD Severity was also assessed. Post hoc analysis was conducted to further define the MCID for the E-RS: COPD total score and the domain scores using GRC anchors. Methods: Daily E-RS: COPD scores were aggregated into 4 week blocks to reduce daily variability in score. We used the change from baseline for E-RS: COPD Week 21 to 24 in the intent-to-treat (ITT) population and Week 49 to 52 in the extension population (EXT) population. Change from baseline was mapped against GRC at week 24 (ITT) and week 52 (EXT). GRC was measured on a 7-point Likert scale from much better to much worse. The analyses reported are independent of treatment effect. 1810 participants in the ITT population received randomised treatment up to week 24. The EXT population of 430 of these patients received up to 52 weeks of treatment. Results: In this large single RCT, change from baseline score corresponding to GRC response of slightly better are generally lower than previously reported values (Leidy et al 2014) of −2 total score, −1 breathlessness and −0.7 for both cough and sputum and chest symptoms domains (table 1). Conclusions: Although MCID values calculated in this analysis, using GRC response of 'slightly better', are generally slightly lower than the published values (Leidy et al 2014, E-RS: COPD user guide 2016); Leidy et al 2014 indicate that the values they report may be conservative estimates. This analysis of a single large RCT would support that conclusion. References: Lipson, et al. Am J Resp Crit Care Med 2017;196(4):438–446. Tabberer, et al. Adv Ther2018;35(1):56–71. Leidy, et al. Respir Res2014;15(1):124. E-RS™: COPD USER MANUAL (v5.0) March 2016. Funding: GSK (study number 116853; NCT02345161 )